Pendekatan Ahli Sunnah wal-Jamaah Hj Mohd Yasin b Muhammad dalam Pendidikan Masyarakat Islam di Negeri Johor: The Approach of Ahli Sunnah Wal-Jamaah by Hj Mohd Yasin B Muhammad in the Education of Society in the State of Johor - Mahyuddin, Muhammad Khairi; Abd Ghani, Zulkiple; Mohamed Ariffin, Mohd Yahya; Sipon, Sapora; Mokhtar, Ahmad Najaa’ (‘Abqari Journal, 2021)
Education is important in Islam. Ahli Sunnah wal-Jamaah is a moderated approach and acknowledged as a prominent school held by the majority Muslim in the Islamic world. Haji Mohd Yasin b. Muhammad is a Malay scholar figure in the state of Johor that had been discovered applying the approach of Ahli Sunnah wal-Jamaah in educating the Islamic society in the said state. This article uses the historical method in clarifying his approach, thought, and contribution in strengthening the education of religion of Islam toward Muslim society in the state of Johor. Based on his efforts, the finding shows that he adopted the education and the practice of the religion of Islam according to the school of Ahli Sunnah wal- Jamaah obviously from the reference of classical authorized books and his belief in preaching the teaching of Islam